Pluralism in Health Law: Examining the Interplay between Customary and Formal Legal Systems in Indonesia and India - Sukrisno, Wijayono Hadi; Arifin, Zainal; Ezenduka, Uzodinma Yurriens (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Legal pluralism in the health sector is an important issue in countries with high social and cultural diversity such as Indonesia and India. Both countries have dual legal systems that combine state formal law with customary law that lives in communities, and the regulation and implementation of health services in practice are often colored by overlapping authority, local cultural values, and differing views on the legitimacy of traditional healing. This phenomenon poses challenges in realizing justice, access, and equity in health services. Purposes of the Research: This research aims to examine in depth the relationship and dynamics between the customary law system and the formal legal system in the context of health law in Indonesia and India. This study seeks to identify forms of interaction, potential conflicts, and opportunities for harmonization between the two legal systems in regulating traditional medicine practices and modern health services. Methods of the Research: This research uses a qualitative approach with comparative study methods and normative legal analysis. Data was collected through literature studies and analysis of laws and regulations. This approach allows mapping the relationship between customary norms and formal law and their influence on national health policy. Results of the Research: The results show that both Indonesia and India face similar challenges in integrating customary law systems with formal health laws. In Indonesia, customary law is constitutionally recognized but has not been fully integrated into health regulations. In India, traditional medicine systems such as Ayurveda and Unani gained stronger legal recognition. The study underscores the importance of an inclusive model of legal pluralism to ensure the protection of public health without neglecting local wisdom.